2017
DOI: 10.1007/s10653-017-9927-4
|View full text |Cite|
|
Sign up to set email alerts
|

Biosolids application affects the competitive sorption and lability of cadmium, copper, nickel, lead, and zinc in fluvial and calcareous soils

Abstract: The objective of this research was to investigate the effects of biosolids on the competitive sorption and lability of the sorbed Cd, Cu, Ni, Pb, and Zn in fluvial and calcareous soils. Competitive sorption isotherms were developed, and the lability of these metals was estimated by DTPA extraction following their sorption. Sorption of all metals was higher in the fluvial than in the calcareous soil. Sorption of Cu and Pb was stronger than that of Cd, Ni, and Zn in all soils. Biosolids application (2.5%) reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The authors attribute these results to the low solubility and availability of Pb in the soil, due to the inherent high organic matter content and the fact that the soil pH is almost neutral. However other studies confirmed the reduced availability of Pb to plants, due to the application of different amendments [50,51]. Several studies on the effect of soil amendments on Zn absorption by plants have mentioned different effects, as these are probably highly dependent on the type of soil and of the amendment, plant species and Zn mass fraction [24,50].…”
Section: Pte Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors attribute these results to the low solubility and availability of Pb in the soil, due to the inherent high organic matter content and the fact that the soil pH is almost neutral. However other studies confirmed the reduced availability of Pb to plants, due to the application of different amendments [50,51]. Several studies on the effect of soil amendments on Zn absorption by plants have mentioned different effects, as these are probably highly dependent on the type of soil and of the amendment, plant species and Zn mass fraction [24,50].…”
Section: Pte Accumulationmentioning
confidence: 99%
“…However other studies confirmed the reduced availability of Pb to plants, due to the application of different amendments [50,51]. Several studies on the effect of soil amendments on Zn absorption by plants have mentioned different effects, as these are probably highly dependent on the type of soil and of the amendment, plant species and Zn mass fraction [24,50].…”
Section: Pte Accumulationmentioning
confidence: 99%
“…S2) and therefore failed to immobilize the Cd via precipitation reactions. Cadmium availability is generally high in weathered and acidic soil with low OM and CEC (Sauvé et al 2000;Shaheen et al 2017;Jalali and Najafi 2018;Mu et al 2019) such as our soil; in these soil conditions, Cd availability is primarily controlled by redox potential (Arao et al 2009;Rinklebe et al 2016;Zhao and Wang 2020). We therefore conclude that higher amendment rates or continued return of rice husk as Biochar or CharSil would be necessary to cause Cd immobilization, likely through raising soil pH (Table 1).…”
Section: Rice As and CD Managementmentioning
confidence: 99%
“…They found that green waste, tree barks, municipal organic waste, and vine shoots which have K d values of Zn ranging from 80 to 1410, 105 to 515, 440 to 1220, and 85 to 2660 L/kg, respectively, are the best materials for environmental remediation that can be used alone or in mixtures to increase soil pH and sorption capacity. Biosolids were studied for their effects on the competitive sorption and lability of Zn in fluvial and calcareous soil (Shaheen et al, 2017). The reported K d values ranged from 16.1 to 1334.9 L/kg for biosolids-amended fluvial soil and 7 to 490.2 L/kg for biosolids-amended calcareous soil.…”
Section: Zinc (Zn)mentioning
confidence: 99%